PENDAMPINGAN AKSELERASI ADOPSI DIGITAL PLATFORM PADA UMKM BIDANG PEMASARAN PERIKANAN - Ningsih, Etik Sulistiowati; Rusma, Nurwahdah; Purnamasari, Elly (Jurnal Abdi Insani, 2024)
In contrast to the 1998 crisis where MSMEs did not experience any shocks, MSMEs during the Covid pandemic experienced very strong shocks. However, MSMEs managed to recover quickly, especially those that integrated their marketing into digital platforms. As part of efforts to accelerate the digitalization of MSMEs, Mulawarman University through the Kedaireka program provides assistance to MSMEs in Samarinda where one of the targets is home culinary MSMEs.  Assistance aims to 1) increase product promotion through business branding, 2) develop products, and 3) register MSMEs on digital platforms. Mentoring methods are carried out personally and collectively. Collectively, MSME players were given training regarding product promotion via digital platforms by resource persons from the Kedaireka Program management. Collective mentoring is followed up with a personal approach by students participating in the Kedaireka program. Personal assistance is carried out face to face by visiting MSME actors for around one month.  The results of the assistance show that the obstacle faced by MSME actors in carrying out product development is the availability of raw materials where fishery raw materials are seasonal. Product promotion efforts carried out through product branding which was carried out by re-creating the business logo were successfully carried out without significant obstacles. Meanwhile, increasing marketing through digital platforms has not been successful due to the limitations of MSME actors in understanding the features and steps for updating product images as well as limitations in producing quality product images or photos. Efforts to accelerate the integration of marketing of fishery products require two conditions, namely product and promotion. In the product aspect, guaranteed availability of fishery products is very necessary for marketing sustainability and customer satisfaction. Meanwhile, in the promotional aspect, the quality of the images uploaded to the digital platform must be eye catching.